PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASI LEMBAGA PERKREDITAN DESA (LPD) - Jaya Wardana, Anak Agung Ngurah Made Bramasta; Supartha, I Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p03, 2024)
The purpose of this study is to analyze the effect of job stress on organizational commitment, to explain the effect of job stress on job satisfaction, to explain the effect of job satisfaction on organizational commitment and to explain job satisfaction in mediating the effect of job stress on organizational commitment. The number of samples used in this study are 34 employees, using the saturataion sample method. Data are analyzed using path analysis. The results showed that work stress has a negative and significant effect on organizational commitment, work stress has a negative and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational commitment, and job satisfaction Mediated the Effect of Job Stress on Organizational Commitment Lembaga Perkreditan Desa (LPD) Padangsambian Pakraman Village in Denpasar City